2012
DOI: 10.1111/j.1745-4557.2012.00459.x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Free Radical Scavenging Activities of Different Plant Parts from Two Erica Species

Abstract: Aqueous extractions from two species of Erica consumed as infusions in several countries to heal ailments were investigated for their phenolic and flavonoid contents, along with antioxidant capacity and radical scavenging capacity using total antioxidant activity, ferric-reducing antioxidant power, reducing power, 1,1diphenyl-2-picrylhydrazyl and 2-2'-azino-bis(3 ethylbenzothiazoline-6-sulfonic acid) radicals, respectively. Antioxidant properties and total phenolic content differed significantly among these pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…The leaves were found to be have the highest total phenolic (30.6 mg GAE/g) and flavonoid (4 mg quercetin equivalent/g) contents. In all tests, the leaves usually showed the highest antioxidant activity [28]. Furthermore, phenylethanoids (RC50= 11.11±10 -2 to 2.44±10 -5 mg/mL) and flavonoids (RC50= 15.6×10 −3 to 17.2×10 −3 mg/mL) obtained from the methanol extract of E. arborea leaf exhibited significant antioxidant capacity in DPPH assay [11,12].…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The leaves were found to be have the highest total phenolic (30.6 mg GAE/g) and flavonoid (4 mg quercetin equivalent/g) contents. In all tests, the leaves usually showed the highest antioxidant activity [28]. Furthermore, phenylethanoids (RC50= 11.11±10 -2 to 2.44±10 -5 mg/mL) and flavonoids (RC50= 15.6×10 −3 to 17.2×10 −3 mg/mL) obtained from the methanol extract of E. arborea leaf exhibited significant antioxidant capacity in DPPH assay [11,12].…”
Section: Resultsmentioning
confidence: 93%
“…Genus Erica has been investigated for their biological acitivites such as antiulcer [17], anti-inflammatory, antinociceptive [18], antimicrobial [16,[19][20][21][22], antilithic [23] and cytotoxic [21,24] activities. There are several reports on the antioxidant activity of Erica species [21,22] except E. arborea [11,12,21,[25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Total phenolic content (TPC), ABTS radical cation scavenging activity (ABTS assay) and DPPH free radical scavenging activity (DPPH assay) were determined regarding the method described previously by Prieto et al (1999), Re et al (1999) and Blois (1958), respectively, with the minor modifications indicated in Nunes et al 2012. In addition, for DPPH assay absolute ethanol (100 %) was used as solvent.…”
Section: Evaluation Of Extractsmentioning
confidence: 99%
“…Aqueous 67 extracts from two species of this plant, Erica australis L. and Erica arborea L., were 68 previously studied by our group and were found to possess relatively high activities, 69 especially concerning the 1,1-Diphenyl-2-picrylhydrazyl (DPPH) radical (IC 50 of 60 70 µg/mL) (Nunes, et al, 2012 The extraction was carried in a Soxhlet device with Electrothermal heating mantles 125 (Electrothermal, Essex, UK), using 0.4 g of plant material and 60 mL of water or methanol.…”
mentioning
confidence: 99%